An emerging theory of the persistence of social class microaggressions: an interpretative phenomenological study. Issue 4 (1st October 2020) - Cook, Jennifer M.; O'Hara, Caroline C.
ABSTRACT: Eleven counselor education doctoral students participated in an Interpretive Phenomenological Analysis study aimed to understand their social class microaggressions (SCMs) experiences. A tentative theory emerged from the data that SCMs persist to preserve homeostasis. The super-ordinate theme, Unequal, Embedded, Societal Structures is corroborated by the subordinate themes, Social Class Invisibility, Intersecting Identities, Perceptions and Assumptions about Social Class, Privilege and Unawareness about Social Class, and SCM Manifestations . Together, the superordinate theme and subsequent subordinate themes culminate in the preservation of homeostasis. We offer a data driven model to depict the theory, present participant data with extensive quotes, counseling implications, future research, and a call to the profession to resist the pull of homeostasis so SCMs no longer serve a socio-cultural purpose to oppress others.